Automorphisms of groups of order p^5 - Pechenyuk О. V.; Pylyavs'ka, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study automorphisms of groups of order p^5 (p is an odd prime number). Groups without any automorphism of order 2 and groups with group automorphisms of order p^6 are found.